Funkcjonowanie aktu życzeń w obszarze public relations – na przykładach z fanpage’ów serwisu społecznościowego Facebook - Joanna Smól, Joanna Smól (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2020)
The analysis included in the article concerns the wishes posted on company profiles on Facebook. The considerations begin with the description of wishes as a speech act that has ritual, etiquette-related and phatic functions. Next, the article discusses the role of social media in communication in the public relations area, particularly as a tool to contact customers. One of the ways of establishing this contact is extending wishes on a company fan page. This is another stage of the evolution of the speech act in question. The analysis of companies’ wishes includes the description of the occasion for extending them, the content of the wishes, the relationship between the sender and the receiver and, in particular, the interaction that results from the very character of wishes as a speech act as well as from the opportunities provided by communication in social media.